2018
DOI: 10.1515/opag-2018-0057
|View full text |Cite
|
Sign up to set email alerts
|

Climate change in Upper East Region of Ghana; challenges existing in farming practices and new mitigation policies

Abstract: Countries and international organizations are making conscious effort to address climate change threat to humanity. Rising fossil fuel burning and land use changes to meet human demands continuously emit large quantities of greenhouse gases into the atmosphere thus causing climate change. The research used Talensi District as a case study to determine factors influencing farmers’ adaptation response and the actual practices used to avert climate change impact. A total of 225 small-scale farmers were sampled fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…Several papers mentioned that cost was even more challenging for women and farmers with fewer assets, smaller parcels of land or lower economic status. At least four papers suggested seed subsidies as a strategy to improve access to seed [35][36][37][38] .…”
Section: Accessmentioning
confidence: 99%
“…Several papers mentioned that cost was even more challenging for women and farmers with fewer assets, smaller parcels of land or lower economic status. At least four papers suggested seed subsidies as a strategy to improve access to seed [35][36][37][38] .…”
Section: Accessmentioning
confidence: 99%
“…According to [33], the main problem encountered by farmers and which leaves them extremely vulnerable and unable to plan is the inadequate weather. [34] made similar observations in Zimbabwe's Seke and Murewa Districts where a significant proportion of farmers had no access to early weather forecasting information.…”
Section: Effects Of Drought and Vulnerability On Food Insecurity: Vulmentioning
confidence: 99%
“…Crop variety diversification and drought-resistant crops or breeds are highlighted as coping strategies. For example, in a study in Malawi [33], researchers found that Malawians increasingly prefer short-season maize as a strategy for adapting to drought. They, therefore, suggested the adoption of maize cultivars that are tolerant to climatic extremes and variability as one possible solution.…”
Section: The Effects Of Adaptation Strategies On Local Farmers In Africamentioning
confidence: 99%
See 2 more Smart Citations